Absorber materials based on polymer nanocomposites containing silver nanoparticles for solar thermal collectors - Asmussen, Silvana Valeria (2018)
This study describes the synthesis and characterization of polymer-based nanocomposites to fabricate absorber materials for solar thermal collectors. Heat generation by nanosized silver particles (NSP) under irradiation with light of appropriate wavelength is exploited for an efficient harvesting of solar energy. NSP were synthesized by reduction of silver nitrate (AgNO3) in a methacrylate resin. The photothermal conversion of solar energy into heat is optimized by increasing the overlap between the plasmonic band of the NSP and the spectral emission of the sun. Thus, the synthesis conditions were adjusted in order to broaden the plasmon absorption band of the resultant NSP. The UV–vis spectra of suspensions containing 300 ppm NSP exhibited a broad absorption band in the range between 360 and 1100 nm with three absorption peaks at 335, 440, and 700 nm. These absorption bands are associated to the presence of triangular NSP, which was confirmed by TEM microscopy. The resins containing NSP were activated with benzoyl peroxide and polymerized after 20 min at 80 °C. The photothermal conversion effect of the nanocomposites was assessed by monitoring the temperature increase with fine thermocouples embedded in 2-mm thick specimens during irradiation with light of different wavelength. The temperature reached during irradiation of nanocomposites showing a very broad absorption band was 115 °C while that of the nanocomposites exhibiting a single peak was 102 °C.